Investigating the Nexus of Psychological Capital with Entrepreneurial Success: The Mediating Role of Burnout - Malak, Sarfraz Ali; Imamuddin Khoso,; Mushtaque Ali Jariko, (IBT- JOURNAL OF BUSINESS STUDIES, 2023)
This research empirically investigates the association of psychological capital (PsyCap) with success of entrepreneurs, and also examines the mediating role of burnout on the relationship between PsyCap and entrepreneurial success. In research design, quantitative methods were employed and cross-sectional data were collected by using random sampling technique through online survey questionnaire adopted from previous studies. The sample size determined through G* power was 134 for this study; however, we got response from 296 entrepreneurs of Sindh province, Pakistan. The data are analyzed in SmartPLS-SEM to assess measurement and structural models, and to compute hypotheses testing results. The findings reveal that PsyCap has positive significant relationship with success of entrepreneurs. This suggests that higher PsyCap abilities ensure more success of entrepreneurs in their entrepreneurial activities. Interestingly, PsyCap reported a negative impact on burnout; means good PsyCap resources reduce the negative effects of burnout among entrepreneurs. Results further indicate that burnout partially mediates the relationship between PsyCap and success; hence shows that entrepreneurs in Pakistan due to more Job demands, risks, and uncertain situations experience burnout which impacts on their success, however, positive PsyCap resources; including resilience and optimism, as well as self-efficacy and hope, work as buffer and ameliorate negative burnout effects and help entrepreneurs in achieving businesses success. The outcomes of this research provide valuable practical implications for countering burnout through fostering PsyCap resources which is important for strengthening entrepreneurship, and adds fresh insights in the existing literature.